2010
DOI: 10.1111/j.1461-0248.2010.01464.x
|View full text |Cite
|
Sign up to set email alerts
|

Integration of molecular functions at the ecosystemic level: breakthroughs and future goals of environmental genomics and post‐genomics

Abstract: Environmental genomics and genome-wide expression approaches deal with large-scale sequence-based information obtained from environmental samples, at organismal, population or community levels. To date, environmental genomics, transcriptomics and proteomics are arguably the most powerful approaches to discover completely novel ecological functions and to link organismal capabilities, organism–environment interactions, functional diversity, ecosystem processes, evolution and Earth history. Thus, environmental g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 91 publications
0
30
0
Order By: Relevance
“…Our culture data support this hypothesis. Genome and metagenome analyses would allow functions to be predicted on a finer scale to assess and hypothesize the individual ecological functions within the analyzed habitat or ecosystem (Vandenkoornhuyse et al, 2010). The detection of fungal sequences at great depths and our success in the cultivation of fungal strains leads us to ask what role they play in deep carbon cycling and what involvement they have in dynamics/regulation of prokaryotic populations, if they are active in situ.…”
Section: Ecological Implications and Future Prospectsmentioning
confidence: 99%
“…Our culture data support this hypothesis. Genome and metagenome analyses would allow functions to be predicted on a finer scale to assess and hypothesize the individual ecological functions within the analyzed habitat or ecosystem (Vandenkoornhuyse et al, 2010). The detection of fungal sequences at great depths and our success in the cultivation of fungal strains leads us to ask what role they play in deep carbon cycling and what involvement they have in dynamics/regulation of prokaryotic populations, if they are active in situ.…”
Section: Ecological Implications and Future Prospectsmentioning
confidence: 99%
“…Finally, the introduction of "omic" methods opens a new area in the assessment of the impact of pesticides on microbial communities. The use of metagenomic, metatranscriptomic and metaproteomic methods in recent years has shown that environmental microbial ecology is already entering the "Omics" era (see for example Nelson et al, 2006;Vandenkoornhuyse et al, 2010). Despite some restrictions, there is no doubt that all these methods will soon be major tools for ecotoxicological studies.…”
Section: Non-pcr Based Molecular Methodsmentioning
confidence: 99%
“…Beveridge et al, 2010;Petchey et al, 1999). Understanding the functional roles of these organisms in situ is far more challenging and until recently they have been confined to a 'black box' in field studies (Purdy et al, 2010;Vandenkoornhuyse et al, 2010), despite early recognition that they are probably the main drivers of most ecosystem processes (e.g. Azam et al, 1983;Finlay and Esteban, 1998;Pomeroy, 1974;Pomeroy et al, 2007).…”
Section: Future Directions: New Responsesmentioning
confidence: 99%